Business elites' attitudes toward taxation and the state: The case of Chile - Jorge Atria; Julius Durán; Simón Ramírez (United Nations Research Institute for Social Development (UNRISD), 2021)
What do the wealthiest groups in society think about tax payment? What is their view of the role of the state? How do these perceptions influence the ways in which the government collects taxes and provides social spending? This paper addresses these questions focusing on the case of Chile. Although Chile is considered one of the countries with highest state capacity in Latin America, its tax policy shares several features with lower-performing countries in the region, such as limited redistribution and a regressive tax structure, showing little ability to tackle economic inequality. Based on extensive analysis of state performance that included a comparison with Uruguay and Portugal as well as 32 in-depth interviews with members of the Chilean economic elite, we show divergences between the quality of government spending and elite perceptions on this issue. Elites' distrust of state action leads to unwillingness to pay taxes, which they see primarily as a cost rather than an instrument to promote solidarity or social cooperation. Taxes are also perceived as too high, though the effective tax rates of high-income taxpayers are on par with that of lower classes. We highlight the need to analyse fiscal performance, taking into account both spending and tax collection-including more opaque indicators such as tax expenditures-and rethink communication strategies to present state performance more clearly
Keywords: 330; Chile; consent; elites; redistribution; taxation